In the lion's den [compact disc, unabridged] - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- House of Falconer., 2020)
James Lionel Falconer has become the right-hand man of the head of London's most prestigious shipping company. Can James continue to be the master of his own fate, even after entering the lion's den?